Semilattices and K-finite objects - Acuña-Ortega, Osvaldo (2017)
We prove that for X Є  ǀEǀ, E elementary topos, the following properties are equivalent: (a) X is K-finite, (b) for every upper semilattice B, the diagonal B → BX has a left adjoint.